2019
DOI: 10.1371/journal.pone.0224410
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of macular ganglion cell layer thickness in foveal hypoplasia: A new diagnostic criterion for ocular albinism

Abstract: Background/AimsTo analyse the distribution of macular ganglion cell layer thickness (GCLT) in patients with foveal hypoplasia (FH) with or without albinism to obtain new insights into visual pathway anomalies in albinos.MethodsPatients with FH who presented at our institution between 2013 and 2018 were retrospectively drawn for analysis. Mean GCLT was calculated after automated segmentation of spectral domain-optical coherence tomography (SD-OCT) scans. Patients with FH due to albinism (n = 13, termed ‘albinis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
5
19
2
1
Order By: Relevance
“…Foveal hypoplasia is characteristic of albinism and is defined by retention of inner retinal layers (including the GCL and IPL) at the incipient fovea, but this study shows unique features of GCL and IPL topography that have not been previously described. Another study (published during peer review of our study) examined GCL topography in albinism and found a “temporal to central shift” in GCL thickness 40 ; thus, our observations largely agree with that study. We expand on the findings of Brücher et al 40 by also describing the IPL and examining these layers in a larger participant cohort.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Foveal hypoplasia is characteristic of albinism and is defined by retention of inner retinal layers (including the GCL and IPL) at the incipient fovea, but this study shows unique features of GCL and IPL topography that have not been previously described. Another study (published during peer review of our study) examined GCL topography in albinism and found a “temporal to central shift” in GCL thickness 40 ; thus, our observations largely agree with that study. We expand on the findings of Brücher et al 40 by also describing the IPL and examining these layers in a larger participant cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Another study (published during peer review of our study) examined GCL topography in albinism and found a “temporal to central shift” in GCL thickness 40 ; thus, our observations largely agree with that study. We expand on the findings of Brücher et al 40 by also describing the IPL and examining these layers in a larger participant cohort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The diagnosis of albinism was based on the recommendation by Kruijt et al 1 as individuals with albinism show variability in clinical signs and may not always present with all of the characteristics associated with the disorder. 1 , 2 , 17 Consequently, Kruijt et al 1 recommend that in the absence of any molecular assessment, the diagnosis of albinism can be made using major and minor clinical diagnostic criteria. The major criteria include ocular (iris and fundus) hypopigmentation, foveal hypoplasia and chiasmal misrouting while the minor criteria include nystagmus, skin and hair hypopigmentation, fundus hypopigmentation and foveal hypoplasia.…”
Section: Methodsmentioning
confidence: 99%
“… 12 , 15 , 16 In albinism, the development and maturation of the visual system and structures therein are altered because of melanin abnormalities. 9 , 15 , 17 Particularly the normal foveal developmental process, which begins early in gestation and continues postnatally, is prematurely arrested in individuals with albinism. 15 , 18 Consequently, foveal hypoplasia, which refers to the fovea being absent or partially developed, is a common clinical characteristic in individuals with albinism.…”
Section: Introductionmentioning
confidence: 99%